2019
DOI: 10.1590/1414-431x20198735
|View full text |Cite
|
Sign up to set email alerts
|

Exosomes secreted from miRNA-29b-modified mesenchymal stem cells repaired spinal cord injury in rats

Abstract: Exosomes, a kind of extracellular vesicle, are promising therapeutic agents for spinal cord injury (SCI). This article aimed to investigate effects of exosomes secreted from miRNA-29b-modified bone marrow mesenchymal stem cells (BMSCs) on SCI. Exosomes were extracted from BMSCs transfected with miRNA-29b or negative control (miR NC). SCI rats were injected intravenously with exosomes (control exosomes, miRNA-29b exosomes) and BMSCs (miR NC, miRNA-29b) through the tail vein. The expression of miRNA-29b in spina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
71
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(76 citation statements)
references
References 36 publications
3
71
0
2
Order By: Relevance
“…Therefore, their secreted exosomes can be good candidates for therapeutic purpose [ 16 ]. An example is bone marrow derived MSC transfected with miR-29b for healing injured spinal cord in rats via exosomes encapsulated miR-29b [ 18 ].…”
Section: Progress In Mirna-enriched Ev Therapiesmentioning
confidence: 99%
“…Therefore, their secreted exosomes can be good candidates for therapeutic purpose [ 16 ]. An example is bone marrow derived MSC transfected with miR-29b for healing injured spinal cord in rats via exosomes encapsulated miR-29b [ 18 ].…”
Section: Progress In Mirna-enriched Ev Therapiesmentioning
confidence: 99%
“…[26] Reports have revealed that rehabilitation of SCI rats achieved satisfactory results via injecting intravenously with exosomes (control exosomes, miRNA-29b exosomes) and BMSCs (miR NC, miRNA-29b) to the tail vein. [27] Li has suggested that exosomes derived from miR-544 modi ed BMSCs exhibited a protective role for the SCI rat model in improving their functional recovery as well as the promotion of neuronal survival. [28] Besides, injection of miR-133b exosomes produces effects in neuron protection, promotion of the axon regeneration, and enhancement of the damaged locomotor function caused by SCI.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment with miR-133b-rich EVs promoted the recovery of hindlimb locomotor function, reduced the lesion volume, protected the neuronal cells and enhanced axon regeneration compared to the EV and control groups. MSCs-derived exosomes also have been modified to transfer miR-29b and miR-216a-5p to promote regeneration of injured spinal cord [ 88 , 89 ]. Interestingly, MSCs-derived exosomes also have been used to deliver phosphatase and tensin homology small interfering RNA (PTEN) that promote neuronal cell growth, support angiogenesis and suppressing gliosis when the exosomes were delivered intranasally to the rat SCI model [ 79 ].…”
Section: Novel Biological Therapies For Spinal Cord Injurymentioning
confidence: 99%